'What lies beyond': Mimesis and transcendence in the portrait poetry and poetic translations of Peter Dane. Issue 1 (1st May 2017) - Franke, Norman P.
A former professor of English, Peter Dane spent the last years of his life as a poet and environmentalist in the Bay of Islands, New Zealand. In his poetry, unlike that of many (post) modern writers, this revolutionary traditionalist celebrated form and beauty as a means of realizing and contemplating the limited and contingent, yet potentially transcendent and universal liberty of the arts. In his portrait poetry, the transcendental 'beyond' is 'firmly rooted in the everyday'. I argue that according to Dane's portrait poems, a poet is not a genius by dint of their superior skill or of their calculating or knowing mind, but on the strength of living the tension between the human experience of transience and the intended but never fully obtainable telos of art, which is not perfection but 'its own indicative stillness [...] and a stillness beyond it'. Assisted by Walter Benjamin's and Lawrence Venuti's theories, this article also looks at Dane's renderings of German poetry into English. For Dane, translation of poetry does not consist primarily in the accurate rendering of propositions or poetic devices but in invoking those 'transcendent moments' that touch and alter our being. Based on readings of Dane's poetry about Michelangelo and August Kekulé and Dane's translation of Novalis' poem 'Wenn nicht mehr Zahlen und Figuren', this article analyses, contextualizes and celebrates Dane's transcendental poetry.